2011
DOI: 10.1093/annonc/mdq303
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of breast cancer in Iran: downstaging without a formal screening program

Abstract: despite the relative improvement in the status of BC patients, the vast majority are diagnosed in advanced stages. Specific screening measures should be implemented in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 19 publications
7
106
0
Order By: Relevance
“…Paucity of data linking probable factors to increased risk of BC in the developing countries is still a problem (Porter, 2009). In Iran, BC is the most common primary cancer among women (24 per 100,000) and the proportion of newly diagnosed cases has gone up, recently (Mousavi et al, 2009;Harirchi et al, 2011). In our study, the percentage of patients diagnosed with BC has risen from 19.8% in 1994 to 25.7% in 2009.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Paucity of data linking probable factors to increased risk of BC in the developing countries is still a problem (Porter, 2009). In Iran, BC is the most common primary cancer among women (24 per 100,000) and the proportion of newly diagnosed cases has gone up, recently (Mousavi et al, 2009;Harirchi et al, 2011). In our study, the percentage of patients diagnosed with BC has risen from 19.8% in 1994 to 25.7% in 2009.…”
Section: Discussionmentioning
confidence: 58%
“…Also, subjects were stratified into five age groups: ≤40 years, 41-50 years, 51-60 years, 61-70 years, and 71≤ years. Cut-off age for young women has varied from 35-40 years in some studies (Fisher et al,1997;Colleoni et al, 2002;Harirchi et al, 2011). We selected 40 years or under, since it provided a group of reasonable size which was compatible with other studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection of breast cancer is the key for decreasing its burden. So, specific screening measures should be implemented for Iranian women and special programs should be considered for younger women (Mousavi et al, 2006;Harirchi et al, 2011). On the other hand Iranian studies indicated that the women's awareness of BC warning signs and effective screening were very inadequate (Yavari and Pourhoseingholi., 2007;Montazeri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to the international reports, an annual 1.15 million cases are identified globally, and 502000 patients die from this disease each year (Harirchi et al, 2011). In Iran, with crude incidence of nearly 24.4% and Age Specific Rate (ASR) of 23.65% in 2006, breast cancer in female population was the most common type of all cancers, and the third cause of mortality (Ebrahimi et al, 2007;Mousavi et al, 2009;Fouladi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%